A SU-8 fluidic microsystem for biological fluids analysis - Ribeiro, J. C. (2004)
This paper describes a fluidic microsystem fabricated in SU-8 for suitable on-chip liquid handling and mixing. Its application is the concentration measurement of biomolecules in biological fluids. The SU-8 fabrication process is a low-cost process, biocompatible, UV lithography semiconductor compatible and not requires expensive masks. Moreover, SU-8 process allows deeps microchannels with very low roughness and suitable for optical absorption measurement.